APPLICATION OF BIOLOGICAL PROTECTION PRODUCTS FOR RAPESEED CULTIVATION IN THE NORTH KAZAKHSTAN REGION - Myrzabaeva , M.T.; Konysbaeva , D.T.; Gadzhimuradova , A.M.; Baibusenov , K.S. (Eurasian Journal of Applied Biotechnology, 2025)
The article is devoted to the biologization of the processes of protection of one of the promising crops in the conditions of Northern Kazakhstan. The authors revealed the potential opportunities among rapeseed producers in the global market, the leaders are the EU countries: 17.26 (10.311 thousand tons); China: 14 (6981 thousand tons); Canada: 12.6 (4275 thousand tons); India: 10.8 (3880 thousand tons); Australia: 6.35 (410 thousand tons). Kazakhstan, with a level of 16.4 million tons/year, also plans to increase rapeseed production. As part of the research, the ways of greening rapeseed protection schemes are considered. The article presents the results of the assessment of the impact of reducing the use of pesticides on the yield and condition of rapeseed crops.The object of the researchwasspringrapeseed of the «Maily Dan» variety, the research was carried out in the field and laboratory conditions at the site of the Scientific-production center for grain farming named after A. Barayev and NAO"S.Seifullin Kazakh agrotechnical research University". The focus was on ecosystem aspects and biological control methods for common pests.This study aims to investigate the effects of an ecologized rapeseed crop protection program that uses less chemical pesticides and incorporates growth activators and biofertilizers to lessen environmental stress and boost plant immunity. The selection of genetically resistant cultivars, seed material preparation, computerized pest monitoring, and the use of chemical and biological plant protection are all aspects of the extensive research of plant biology and defensive mechanisms. Integrated plant protection is nearly as expensive as chemical protection, according to studies. Comprehensive protection, on the other hand, has a noticeable environmental benefit, enhances product quality, lowers climatic risks, boosts yield by 10–30%, and has a longer-lasting effect.